The Future of Public Organizations - Aykaç, Burhan; Metin, Hatice (ELSEVIER SCIENCE BV, SARA BURGERHARTSTRAAT 25, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2012)
Public administration as both an academic discipline and a field of practice is subject to a process of change on several accounts such as philosophy, structure and mechanism. In this context the public organizations as the most important component of public administration are considerably affected by this process. These organisations as appointed public service managers which are formalized by strict regulations have undergone a development process parallel to that of states. In the present conditions, what the concept of "the future of public organizations" refers is the new perspectives that these organizations will gain in terms of the structures and mechanisms they have. In this process of change, the effects of globalisation process which created a great pressure on public organizations for change must also be taken into account. The effects of this pressure on public organizations are experienced in different levels depending upon the development levels of different countries. In the literature on public organizations there are some general acceptances about the nature of the change. According to these acceptances, the partnership between public and private sectors will develop, the principles of private sector will be applied in public sector, e-government implementations will play an important role in the public sector operations and so on. So the aim of this study is to assess the projections on public organizations which are supposed to be realized in future. In the assessment the factors such as the organization structures, the concept of new public service and the international developments in administrative terms are used as the means of the examination and the future of public organizations is described.
Keywords: public organization; public administration; globalization; new public management; change